Barriers and preferences in advance care planning: a mixed-methods study of end-stage kidney disease patients and caregivers in India - Bharathi Naik; Anuja Damani; Arun Ghoshal; Shankar Prasad Nagaraju; Pankaj Singhai; Swathi Nayak Ammunje; Ravindra Prabhu Attur; Naveen Salins (BMC Nephrology)
Abstract Objectives To understand preferences for illness-related information, decision-making roles, and barriers to Advance Care Planning (ACP) documentation among patients with End-stage Kidney Disease (ESKD) and their caregivers in India. Methods A convergent parallel mixed-methods study was conducted from October 2022 to September 2023 at a tertiary care hospital in South India. Quantitative data were collected using a validated ACP questionnaire from 247 patient-caregiver dyads. Qualitative data were obtained from semi-structured interviews with 34 patients and 6 caregivers. Quantitative data were analyzed using descriptive and inferential statistics; qualitative data were analyzed thematically using Braun and Clarke’s framework. Results Most patients (90.7%) and caregivers (94.1%) preferred detailed illness-related information, yet ACP documentation interest was low (20.4% dialysis, 9.2% non-dialysis patients). The majority preferred collaborative decision-making involving family and clinicians. Barriers to ACP included limited awareness, emotional burden, and systemic challenges. Enablers included family support and provider guidance. Conclusions While interest in illness information and shared decision-making is high, ACP documentation remains limited. Tailored strategies are needed to promote ACP engagement. Practice implications Integrating culturally sensitive ACP discussions into routine nephrology care and involving families can improve ACP participation.